How a Policy Network Matters for Refugee Protection: A Case Study of Japan's Refugee Resettlement Programme. (17th June 2021) - Akashi, Junichi
Abstract: In 2010, Japan became the first Asian country to launch a refugee resettlement programme. The programme continues today, and the government expanded the scheme to accept more refugees through the resettlement channel in 2020. How Japan, a country known for its reluctance to accept refugees, has strengthened its commitment to its refugee resettlement programme has been insufficiently investigated. Based on surveys of literature that mainly involved primary resources and interviews with key stakeholders of the programmes, this study reveals that the development of a policy network that mediates local constraints on refugee protection processes is a key determinant of the state's capability to accept refugees as well as how well the refugee protection programme functions. Retracing the decade-long history of Japan's resettlement programme, this study argues that the performance of the programme has hinged on local actors and in part on a non-governmental organisation that acts as an intermediary between the state and municipalities, whereas institutional settings in Japan remain the greatest hindrance to the effective participation of NGOs in national humanitarian initiatives.